Sistema experto utilizando lógica difusa para diagnosticar problemas de desnutrición en apoyo al Programa Social Qaliwarma-Provincia de Ascope - Pozo Vera, Oscar Eduardo (2018)
The objective of this research work is to implement an expert system for the diagnosis of malnutrition in infants under five years of age, using the fuzzy logic for the quantification of variables (symptoms) which can not be parameterized._x000D_ The project consists of three stages, the first is in the conceptualization and design of the inference engine supported by an expert from the Qali Warmi social program located in the city from which he laid the main facts (knowledge of child malnutrition). The second stage is the development of a software that reflects the entire inference engine design accompanied by a graphical user interface, so that the tool created serves a more open to users. The third and final stage involves the entire process of implementation of the software developed, applying to infants under 5 years of the Ascope district._x000D_ Whose accurate diagnostic results exceeded the acceptance by medical experts and thus achieving the objective of developing an expert system focused on child malnutrition